KONVERGENSI PERTUMBUHAN EKONOMI DI PROVINSI BENGKULU - Yonas Muzani; Benardin Benardin (Convergence: The Journal of Economic Development, 2019)
This study aims to determine whether or not Sigma Convergence occurs Districts and cities in Bengkulu Province in 2013-2017. The variables used in this study are the dependent variables namely economic growth and independent variables gross regional domestic. The method used in this study is to use sigma convergence analysis using the Microsoft Excel. The type of data used in this study is secondary data sourced from the Central Bureau of Statistics. Based on the results of sigma convergence analysis, it can be said that there has been a sigma convergence between regencies/cities in Bengkulu Province in 2013-2017, it can be seen from the results of the variation coefficient values every year. Keywords:  Convergence, Economic Growth